(3GdPQjI GdWGgQIs - (3eMeO Hf CMeO Hf MeGO Hf SYO Hf eSde, CHh HTQ GdCfUGQj, HGdhdGA, GdQGRj GdOhdGHj GdhQGb,J (B310 (3g` s ((3fUQ Gddg Hf YHO GdefYe Hf fUQ Gddg GHf LhGQi GdJfhNi GdMfai s)
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3CMHQfG GdGejQ GdCLd GdcHjQ GdSjO GdTQja TgGH GdOjf CHh eMeO GdMSf Hf Ydi GdeQGVi GdMSfi GdYdhi QMeg Gddg JYGdi ZjQ eQg s
(3BNQgG (B:s
(3BNQ cJGH GdPQjI Ydjge GdSdGe s
(3HBNQgG SeGYGJ hahGFO Ydi GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B308 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B152 s
Keywords: (3GdJGQjNs